Incidence of childhood burn injuries and modifiable household risk factors in rural Ghana: A cluster-randomized, population-based, household survey. Issue 4 (June 2021) - Mehta, Kajal; Gyedu, Adam; Otupiri, Easmon; Donkor, Peter; Mock, Charles; Stewart, Barclay
Highlights: Burns are a common cause of childhood injury in rural Ghana. The majority of rural households in Ghana have unsafe cooking arrangements, easily accessible to young children. There may be opportunities to reduce the risk of household burn injuries in rural settings. Abstract: Background: We aimed to determine the incidence of childhood burn injuries in rural Ghana and describe modifiable household risk factors to inform prevention initiatives. Methods: We performed a cluster-randomized, population-based survey of caregivers of children in a rural district in Ghana, representing 2713 households and 14, 032 children. Caregivers were interviewed regarding childhood burn injuries within the past 6 months and household risk factors. Results: 357 households were sampled. Most used an open fire with biomass fuel for cooking (85.8%). Households rarely cooked in a separate kitchen (10%). Stove height was commonly within reach of children under five years (<1 m; 96.0%). The weighted annualized incidence of CBI was 63 per 1000 child-years (6.4% of children per year); reported mean age was 4.4 years (SD 4.0). The most common etiology was flame burn. Older age (OR 0.89, 95% CI 0.8–1.0) and households with an older sibling ≥12 years (OR 0.58, 95% CI 0.3–1.3) seemed to be associated with lower odds of CBI. Conclusions: Childhood burn injury is common in rural Ghana. Opportunities exist to reduce the risk of childhood burn injury childhood burns in rural settings by supporting the transition to safer cooking arrangements, child barrier apparatuses in homes without older children, and/or development of formal childcare programs.